Keadilan Hukum Jeremy Bentham dan Relevansinya bagi Praktik Hukum Kontemporer - Frederikus Fios (Humaniora, 2012)
Fair punishment for a condemned has been long debated in the universe of discourse of law and global politics. The debate on the philosophical level was no less lively. Many schools of thought philosophy question, investigate, reflect and assess systematically the ideal model for the subject just punishment in violation of the law. One of the interesting and urgent legal thought Jeremy Bentham, a British philosopher renowned trying to provide a solution in the middle of the debate was the doctrine or theory of utilitarianism. The core idea is that the fair punishment should be a concern for happiness of a condemned itself, and not just for revenge. Bentham thought has relevance in several dimensions such as dimensions of humanism, moral and utility.